Uma perspectiva funcionalista sobre a multifuncionalidade do conector 'MAS' em reportagens e cartas de leitores da Revista Veja - Santos, Danielle Brancalhão dos (2011)
This work presents an analysis of the use of the connector 'but' on textual distinct genres: a report and the reader's letter. In the composition of the corpus, we used the publications of Veja magazine, selecting 113 occurrences of the item in the study on the most commented reports and their reader's letter. Our goal is to analyse if the linguistic structure 'but' suffer any kind of influence from textual genres, moreover analising sintatic and semantical aspects of this connector. Our research is based on the Linguistic Functionalism, because this allows us to establish a relationship between usage and grammar rules, and compare the functionalist theory to the theory of traditional grammars with regard to coordination, the conjunctions and specifically, the breaker 'but'. Some parameters related to the use of this conjunction were analyzed: the occurrence of shared subject and how it was established - by pronoun, noun phrase, zero anaphora or not sharing, the textual extent linked to the sentence introduced by the connector - if it is just another sentence, an statement or a noun phrase, the share of tense between the related sentences and the semantic value acquired by the connector in each context, as proposed by Neves (1984). Was possible to observe in our study new uses of the connector 'but', which mark the evolution of the language in use and new uses in relation to what is covered by the traditional normative grammars.